Bright shadow - Avi, 1937- (New York : Bradbury Press, 1985)
Having used four of the five wishes she is granted to make on behalf of the hapless citizens of her country, Morwenna flees the kingdom to decide what to do with the last wish.
Bulletin (Center for Children's books).
School Library Journal.
5.0
5.0
5-8.
5-8
Keywords: Fantasy; Fantastic fiction